The Effect of Using the Pentagram Strategy as a Modern Tool for Teaching the Chest Pass and Layup Skills in Basketball for Juniors Under 14 Years Old - Harz, Abeer Abbas; Abdulrazzaq, Laith Mohammed (Journal of Physical Education, 2026)
The purpose of this study was to investigate the effect of Pentagram strategy as a contemporary approach in teaching chest pass and layup skills of basketball among under 14 years junior students. The researcher employed experimental method with equivalent groups (experimental and control) with pre-test and post-test. The sample of the study was composed of 16 players from the specialized school of Youth and Sports Ministry that was divided into two groups. The experimental group received a program of 24 instruction units, three per week, using the Pentagram strategy where the skills are divided into five dimensions and developed progressively. The findings indicated that significant differences at chest pass and layup skills were found in favor of the experimental group, and Pentagram intervention program gives also a positive contribute to juniors’s skill performance. The researcher suggested that this plan should be adopted in the educational programs of basic motor skills since it positively affects active thinking, cooperation work and the students’ self-motivation.